Mechanical properties, morphology, and hydrolytic degradation behavior of polylactic acid / natural rubber blends - Buys, Yose Fachmi; Aznan, Aisyah Nur Atiqah; Anuar, Hazleen (IOP Publishing Ltd., 2018)
Due to its biodegradability and renewability, polylactic acid (PLA) has been receiving enormous attention as a potential candidate to replace petroleum based polymers. However, PLA has limitation due to its inherent brittleness. In order to overcome this limitation, blending PLA with elastomeric materials such as natural rubber (NR) are commonly reported. In previous, several researches on PLA/NR blend had been reported, with most of them evaluated the mechanical properties. On the other hand, study of degradation behavior is significance of importance, as controlling materials degradation is required in some applications. This research studied the effect of blend composition on mechanical properties, morphology development, and hydrolytic degradation behavior of PLA/NR blends. Various compositions of PLA/NR blends were prepared by melt blending technique. Tensile test and impact test of the blends were performed to evaluate the mechanical properties. Addition of NR improved the elongation at break and impact strength of the blends, but reduced the tensile strength and stiffness of the specimens. Dynamic Mechanical Analysis (DMA) measurements of the blends displayed two peaks at temperature -70˚C which corresponded to Tg of NR and 65˚C which corresponded to Tg of PLA. Field Emission Scanning Electron Microscopy (FESEM) micrograph of 70/30 PLA/NR specimen also showed two distinct phases, which lead to indication that PLA/NR blends are immiscible. Hydrolytic degradation behavior was evaluated by measuring the remaining weight of the samples immersed in sodium hydroxide solution for a predetermined times. It was shown that the degradation behavior of PLA/NR blends is affected by composition of the blends, with 100 PLA and 70/30 PLA/NR blend showed the fastest degradation rate and 100 NR displayed the slowest one.